Proposta para adequação da gestão dos leitos SUS de Obstetrícia no município de Vitória da Conquista - Andrade, Carlos Alberto Ferraz de; Rodrigues, Flávia Madalena Neves Cardim; Silveira, Glicia Miranda da; Baleeiro, Ilca dos Santos; Silva, José Gustavo Cabral da; Menezes, Luciana Borges; Barros, Luciana Soares de; Cincurá, Rosana Nogueira Santana; Lima, Taiane Tigre (Revista Acadêmica GUETO, 2024)
Projeto